2021
DOI: 10.3389/fneur.2021.736563
|View full text |Cite
|
Sign up to set email alerts
|

Transient Global Amnesia (TGA): Younger Age and Absence of Cerebral Microangiopathy Are Potentially Predisposing Factors for TGA Recurrence

Abstract: Background: Transient global amnesia (TGA) is defined by an acute memory disturbance of unclear etiology for a period of less than 24 h. TGA occurs as a single event in most cases. Prevalence rates of recurrent TGA vary widely from 5.4 to 27.1%. This retrospective study aimed to determine predictors for TGA recurrence.Methods: Cardiovascular risk profile and magnetic resonance imaging (MRI) of 340 hospitalized TGA patients between 2011 and 2020 were retrospectively analyzed. The median follow-up period amounte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…Patients who did not meet the diagnostic criteria were not included in the study. This investigation represents an extension of the cohort from previously reported studies [ 6 , 21 ]. All patients having a discharge diagnosis of TGA during the relevant period were included.…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations
“…Patients who did not meet the diagnostic criteria were not included in the study. This investigation represents an extension of the cohort from previously reported studies [ 6 , 21 ]. All patients having a discharge diagnosis of TGA during the relevant period were included.…”
Section: Methodsmentioning
confidence: 94%
“…The aim of the present study was to analyse sex-specific differences of TGA patients in a large retrospective cohort of a tertiary referral centre. In previous studies, we were able to show differences between TGA patients and acute stroke patients as well as differences between TGA patients with and without subsequent recurrence [ 6 , 21 ]. It was shown that TGA patients, regardless of sex, had significantly higher blood pressure values on admission compared to acute stroke patients, but were less likely to present with signs of chronic hypertension [ 21 ].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, there was only a weak relationship between recurrence and a family history of dementia and a personal history of head injury [ 128 ]. In a recent study of 340 German TGA patients with a follow-up of at least five years, patients with TGA recurrence were significantly younger and had less extent of cerebral microangiopathy than patients with isolated TGA episodes [ 129 ]. Specifically, patients up to 70 years of age without microangiopathic changes on MRI (Fazekas’ score 0) had a 24.5% risk of subsequent TGA recurrence over the next five years [ 129 ].…”
Section: Long-term Outcomementioning
confidence: 99%